Non-coding RNAs in the pathophysiology of heart failure with preserved ejection fraction - Jalink, Elisabeth A.; Schonk, Amber W.; Boon, Reinier A.; Juni, Rio P. (Frontiers in Cardiovascular Medicine, 2024)
Heart failure with preserved ejection fraction (HFpEF) in the largest unmet clinical need in cardiovascular medicine. Despite decades of research, the treatment option for HFpEF is still limited, indicating our ongoing incomplete understanding on the underlying molecular mechanisms. Non-coding RNAs, comprising of microRNAs (miRNAs), long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs), are non-protein coding RNA transcripts, which are implicated in various cardiovascular diseases. However, their role in the pathogenesis of HFpEF is unknown. Here, we discuss the role of miRNAs, lncRNAs and circRNAs that are involved in the pathophysiology of HFpEF, namely microvascular dysfunction, inflammation, diastolic dysfunction and cardiac fibrosis. We interrogated clinical evidence and dissected the molecular mechanisms of the ncRNAs by looking at the relevant in vivo and in vitro models that mimic the co-morbidities in patients with HFpEF. Finally, we discuss the potential of ncRNAs as biomarkers and potential novel therapeutic targets for future HFpEF treatment.